A Double-Blind Randomized Clinical Trial on the Efficacy of Cortical Direct Current Stimulation for the Treatment of Alzheimer’s Disease - Khedr, Eman M.; Gamal, Nageh F. El; El-Fetoh, Noha Abo; Khalifa, Hosam; Ahmed, Elham M.; Ali, Anwer M.; Noaman, Mostafa; El-Baki, Ahmed Abd; Karim, Ahmed A. (Frontiers in Aging Neuroscience, 2014)
Background: The purpose of this study was to investigate the long-term efficacy of transcranial direct current stimulation (tDCS) in the neurorehabilitation of Alzheimer’s disease (AD). Methods: 34 AD patients were randomly assigned to three groups: anodal, cathodal and sham tDCS. Stimulation was applied over the left dorsolateral prefrontal cortex (DLPFC) for 25 minutes at 2mA, daily for 10 days. Each patient was submitted to the following psychometric assessments: Minimental State Examination (MMSE) and Wechsler adult intelligence scale - third edition (WAIS-III) at base line, at the end of the 10th sessions and then at 1 and 2 months after the end of the sessions. Motor cortical excitability and the P300 event related potential were assessed at baseline and after the last tDCS session. Results: Significant TREATMENT GROUP x TIME interactions were observed for the MMSE and performance IQ of the WAIS-III. Post hoc comparisons showed that both anodal and cathodal tDCS improved MMSE in contrast to sham tDCS. whereas this was only true for cathodal tDCS in the performance IQ. Remarkably, tDCS also reduced the P300 latency, but had no effect on motor cortex excitability. Conclusion: Our findings reveal that repeated sessions of tDCS could not only improve cognitive function but also reduce the P300 latency, which is known to be pathologically increased in AD.